National Standards of Education in Contents Standards and Education Process Standards in Indonesia - Helda Helda; Syahrani (CV. ADIBA AISHA AMIRA, 2022)
Education is an important aspect in nation building. However, educational attainment in Indonesia at present has not yet reached the best quality of education. Various policies in an effort to improve the quality of education have been carried out by the government and are still continuing. National Education Standards (SNP) are minimum criteria regarding various relevant aspects in the implementation of the national education system and must be met by education providers and/or units throughout the jurisdiction of the Unitary State of the Republic of Indonesia. National Education Standards serve as the basis for planning, implementing, and supervising education in the context of realizing quality national education. National Education Standards aim to ensure the quality of national education in the context of educating the nation's life and shaping the character and civilization of a dignified nation. National Education Standards are refined in a planned, directed, and sustainable manner in accordance with the changing demands of local, national, and global life. There are eight National Education Standards, namely: Content Standards, Process Standards, Educators and Education Personnel Standards, Facilities and Infrastructure Standards, Management Standards, Financing Standards, and Educational Assessment Standards